PENCEGAHAN PENYALAHGUNAAN NARKOBA DENGAN LAYANAN INFORMASI OLEH GURU BIMBINGAN DAN KONSELING DI SMPN 3 BANJARBARU - Wulandari Wulandari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
This study aims to determine the prevention of abuse with information services by teachers Guidance and Counseling with the formulation of the problem of how the form of prevention of drug abuse with information services and what are the factors that support and inhibit the prevention of drugs with information services in SMPN 3 Banjarbaru. The research is descriptive qualitative research.Prevention of drug abuse in the environment pesrta educated done because of the many cases of drugs that occur within the environment of learners, many of the users are teenagers included in school age. The purpose of this study is to determine the prevention of drug abuse conducted by teachers Guidance and Counseling in SMPN 3 Banjarbaru. Data collection techniques used are observation, interview and documentation.The results of the research are forms of prevention of drug abuse done by emphasizing the effects of the dangers of drugs with material-mateti covering the types of drugs, due to drug abuse, drugs in the view of Islam and the way rejection of drug supply situation. Supporting factors in the prevention of drug abuse with information services include the availability of halls, electronic media, books